2022
DOI: 10.15377/2409-9813.2021.08.3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Plant Trait Biometrics for Paired Invasive and Non-Invasive Species to Magnetized Seed and Watering Treatments

Abstract: A greenhouse study evaluated the widely held hypothesis that invasive plant species have a quicker or stronger response to environmental stimuli such as magnetized irrigation water treatments. A second study objective was to test whether the polarity of magnetized water affected the responses for invasive and non-invasive plant species. Six invasive and six non-invasive plant species were stimulated by magnetizing the seeds followed by applying several magnetized water treatments to the germinated seeds. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…The proton ring spin alignment postulate is indirectly confirmed in several magnetized water studies that revealed that the magnetic polarity of irrigated water can affect plant growth. Several studies that used magnetized water exposed to the South Pole face of the magnets increased plant growth [26][27][28][29].…”
Section: Structured Water Generation Methodsmentioning
confidence: 99%
“…The proton ring spin alignment postulate is indirectly confirmed in several magnetized water studies that revealed that the magnetic polarity of irrigated water can affect plant growth. Several studies that used magnetized water exposed to the South Pole face of the magnets increased plant growth [26][27][28][29].…”
Section: Structured Water Generation Methodsmentioning
confidence: 99%